An Investigation Of The Design Criteria Of Dog Parks - DUYAN, Ahmet Emre; CAYMAZ, Gökçen Firdevs YÜCEL (Architecture Image Studies, 2023)
The increase in the rate of dog ownership and the need for parks has led to an increase in the demand for dog parks and an increase in the countries where dog parks already exist. Dog parks are areas that serve to meet the social and behavioural needs of dogs beyond the private areas of the home, as well as providing opportunities for dogs to establish healthy communication with their owners and other dogs. The aim of this study is to determine how a successful dog park design criteria should be. For this purpose, dog parks were examined under the headings of planning (accessibility, location, car parking and roads, other facilities) and design (entrances and exits, gates, boundaries, surface materials, activity areas, park furniture, planting). As a study method, images, videos, articles, web pages, magazines, books in the internet database were used; then a checklist was created. The checklist was analysed in Hondo, Central and River Bend dog parks in the USA. As a result of the study, it was determined that River Bend Park is inadequate in planning compared to other parks; there are deficiencies in park furniture in all three parks.